Quality of Inpatient Pediatric Case Management for Four Leading Causes of Child Mortality at Six Government-Run Ugandan Hospitals - Sears, David; Mpimbaza, Arthur; Kigozi, Ruth; Sserwanga, Asadu; Chang, Michelle A.; Kapella, Bryan K.; Yoon, Steven; Kamya, Moses R.; Dorsey, Grant; Ruel, Theodore (PLoS One, 2015)
A better understanding of case management practices is required to improve inpatient pediatric care in resource-limited settings. Here we utilize data from a unique health facilitybased surveillance system at six Ugandan hospitals to evaluate the quality of pediatric case management and the factors associated with appropriate care. Methods All children up to the age of 14 years admitted to six district or regional hospitals over 15 months were included in the study. Four case management categories were defined for analysis: suspected malaria, selected illnesses requiring antibiotics, suspected anemia, and diarrhea. The quality of case management for each category was determined by comparing recorded treatments with evidence-based best practices as defined in national guidelines. Associations between variables of interest and the receipt of appropriate case management were estimated using multivariable logistic regression. Results A total of 30,351 admissions were screened for inclusion in the analysis. Ninety-two percent of children met criteria for suspected malaria and 81% received appropriate case management. Thirty-two percent of children had selected illnesses requiring antibiotics and 89% received appropriate antibiotics. Thirty percent of children met criteria for suspected anemia and 38% received appropriate case management. Twelve percent of children had diarrhea and 18% received appropriate case management. Multivariable logistic regression revealed large differences in the quality of care between health facilities. There was also a strong association between a positive malaria diagnostic test result and the odds of receiving appropriate case management for comorbid non-malarial illnesses - children with a positive malaria test were more likely to receive appropriate care for anemia and less likely for illnesses requiring antibiotics and diarrhea. Conclusions Appropriate management of suspected anemia and diarrhea occurred infrequently. Pediatric quality improvement initiatives should target deficiencies in care unique to each health facility, and interventions should focus on the simultaneous management of multiple diagnoses.
Keywords: Pediatric Case Management; Child Mortality; Government-Run Ugandan Hospitals